Respuesta :
Answer:
2,4
Step-by-step explanation:
This question is quite simple. First you need to find the factors of 8. Then you need to see which factors of positive 8 can add up to make -6. The factors are -4 and -2. Then expand. Now you have the equation x^2-4x-2x+8. Now group it.
(x^2-4x) +(-2x+8)
Then take out the X from the first group and the -2 from the second. We want the values in the brackets to be the same.
Now you have
x(x-4)-2(x-4)
Take the x and the -2x and make it a group. Now you have (x-4)(x-2)
Set x-4 equal to zero. x-4=0 Now solve it like a regular equation. Add four to both sides. Now you have x=4
Do the same thing with (x-2) and you get x=2
4 and 2 are your solutions
Answer:
x = 4 and x = 2
Step-by-step explanation:
The easiest way to find the roots is by converting the function into its factored form. This can be determined by asking the question:
What two numbers have a product 8 and a sum of -6?
These two values are -4 and -2.
-4 x -2 = 8
-4 + (-2) = -6
These two numbers are used in the factored form of the equation. You can prove the accuracy of the factored form by re-expanding it (multiply all the terms in the first parentheses by the terms in the second parentheses). The factored form looks like this:
(x - 4)(x - 2)
The roots are the values that make the expression equal 0. This can be done by setting each parentheses equal to 0 and solving for "x".
x - 4 = 0 x - 2 = 0
x = 4 x = 2
Therefore, the roots of the function x² - 6x + 8 are x = 4 and x = 2.